Political Confidence and Democracy in Europe : Antecedents and Consequences of Citizens' Confidence in Representative and Regulative Institutions and Authorities /: Antecedents and Consequences of Citizens' Confidence in Representative and Regulative Institutions and Authorities. ([2019]) - Schnaudt, Christian
No abstract available